ADAPTASI MASYARAKAT BAJO TERHADAP PERUBAHAN LINGKUNGAN DI TELUK BALIKPAPAN - Muhammad Ramli; Endratno Budi Santosa; Agustina Nurul Hidayati (TATALOKA, 2018)
This article trying to identify the Bajo people’s adaptation capacity regarding environmental change through vulnerable capacity index calculation and comparative analyze as well. Using indepth interview and fish bone diagram approaching, this research trying to find out the connectivity between new spreading industry activities, environmental change, and how the people can adapt.  We choosing of three Bajo people settlements, located around Balikpapan Bay as the cases study, and also using nine variables of vulnerable society. As the results, we can find if there were some significant physical-environment changes both  on quality and quantity aspects. After calculating vulnerability index, it shows that level of adaptation capacity at Penajam village better than its on Jenebora and Pantai Lango village as well.